Relationship between preoperative fluid therapy and the occurrence of nausea and vomiting in post-spinal anesthetic patients - Rahmawati, Dian; Lumadi, Sih Ageng; Handian, Feriana Ira (The Journal of Palembang Nursing Studies, 2023)
Background: Spinal anesthesia can cause a significant decrease in blood pressure and increased vagal tone, leading to bradycardia, nausea, and vomiting. To mitigate the risk of nausea and vomiting, it is important to provide appropriate fluid therapy during fasting or anesthesia. Objective: This study aims to determine the relationship between preoperative fluid therapy and the occurrence of nausea and vomiting events in post-spinal anesthetic patients at Dr. Saiful Anwar Hospital, Malang. Methods: This research employed an observational analytic design with a cross-sectional approach. A purposive sampling technique was used, and 50 respondents were selected. The research instrument included the Rhodes Index of Nausea, Vomiting, and Retching (RINVR) observation sheet and fluid calculation formulas. The statistical test employed was Spearman’s rho with a 95% confidence interval (CI) or a significant level value (?) of 0.05.  Results: The results showed that 52% of respondents did not experience nausea and vomiting, 44% experienced mild nausea and vomiting, and 4% experienced moderate nausea and vomiting. The Spearman Rank statistical test yielded a p-value of < 0.0001. Conclusions: In conclusion, there was a significant relationship between preoperative fluid therapy and the incidence of nausea and vomiting in post-spinal anesthesia patients. Therefore, administering adequate fluids before spinal anesthesia can reduce the risk of complications, such as nausea and vomiting, associated with spinal anesthesia.